COVID-19 and neurointerventional service worldwide: a survey of the European Society of Minimally Invasive Neurological Therapy (ESMINT), the Society of NeuroInterventional Surgery (SNIS), the Sociedad Iberolatinoamericana de Neuroradiologia Diagnostica y Terapeutica (SILAN), the Society of Vascular and Interventional Neurology (SVIN), and the World Federation of Interventional and Therapeutic Neuroradiology (WFITN). (16th June 2020) - Fiehler, Jens; Brouwer, Patrick; Díaz, Carlos; Hirsch, Joshua A; Kulcsar, Zsolt; Liebeskind, David; Linfante, Italo; Lylyk, Pedro; Mack, William J; Milburn, James; Nogueira, Raul; Orbach, Darren B; et al.
Abstract : Background: This survey was focused on the provision of neurointerventional services, the current practices of managing patients under COVID-19 conditions, and the expectations for the future. Methods: Invitations for this survey were sent out as a collaborative effort of the European Society of Minimally Invasive Neurological Therapy (ESMINT), the Society of NeuroInterventional Surgery (SNIS), the Sociedad Iberolatinoamericana de Neuroradiologia Diagnostica y Terapeutica (SILAN), the Society of Vascular and Interventional Neurology (SVIN), and the World Federation of Interventional and Therapeutic Neuroradiology (WFITN). Results: Overall, 475 participants from 61 countries responded (six from Africa (1%), 81 from Asia (17%), 156 from Europe (33%), 53 from Latin America (11%), and 172 from North America (11%)). The majority of participants (96%) reported being able to provide emergency services, though 26% of these reported limited resources. A decrease in emergency procedures was reported by 69% of participants (52% in ischemic and hemorrhagic stroke, 11% ischemic, and 6% hemorrhagic stroke alone). Only 4% reported an increase in emergency cases. The emerging need for social distancing and the rapid adoption of remote communication was reflected in the interest in establishing case discussion forums (43%), general online forums (37%), and access to angio video streaming for live mentoring and support (33%). Conclusion: Neurointerventional emergency services are available in almost all centers, while the number of emergency patients is markedly decreased. Half of the participants have abandoned neurointerventions in non-emergent situations. There are considerable variations in the management of neurointerventions and in the expectations for the future.